You are here
Homealgebraic definition of a lattice
Primary tabs
algebraic definition of a lattice
The parent entry defines a lattice as a relational structure (a poset) satisfying the condition that every pair of elements has a supremum and an infimum. Alternatively and equivalently, a lattice $L$ can be a defined directly as an algebraic structure with two binary operations called meet $\wedge$ and join $\vee$ satisfying the following conditions:

(idempotency of $\vee$ and $\wedge$): for each $a\in L$, $a\vee a=a\wedge a=a$;

(commutativity of $\vee$ and $\wedge$): for every $a,b\in L$, $a\vee b=b\vee a$ and $a\wedge b=b\wedge a$;

(associativity of $\vee$ and $\wedge$): for every $a,b,c\in L$, $a\vee(b\vee c)=(a\vee b)\vee c$ and $a\wedge(b\wedge c)=(a\wedge b)\wedge c$; and

(absorption): for every $a,b\in L$, $a\wedge(a\vee b)=a$ and $a\vee(a\wedge b)=a$.
It is easy to see that this definition is equivalent to the one given in the parent, as follows: define a binary relation $\leq$ on $L$ such that
$a\leq b\quad\mbox{ iff }\quad a\vee b=b.$ 
Then $\leq$ is reflexive by the idempotency of $\vee$. Next, if $a\leq b$ and $b\leq a$, then $a=a\vee b=b$, so $\leq$ is antisymmetric. Finally, if $a\leq b$ and $b\leq c$, then $a\vee c=a\vee(b\vee c)=(a\vee b)\vee c=b\vee c=c$, and therefore $a\leq c$. So $\leq$ is transitive. This shows that $\leq$ is a partial order on $L$. For any $a,b\in L$, $a\vee(a\vee b)=(a\vee a)\vee b=a\vee b$ so that $a\leq a\vee b$. Similarly, $b\leq a\vee b$. If $a\leq c$ and $b\leq c$, then $(a\vee b)\vee c=a\vee(b\vee c)=a\vee c=c$. This shows that $a\vee b$ is the supremum of $a$ and $b$. Similarly, $a\wedge b$ is the infimum of $a$ and $b$.
Conversely, if $(L,\leq)$ is defined as in the parent entry, then by defining
$a\vee b=\sup\{a,b\}\quad\mbox{ and }\quad a\wedge b=\inf\{a,b\},$ 
the four conditions above are satisfied. For example, let us show one of the absorption laws: $a\vee(a\wedge b)=a$. Let $c=\inf\{a,b\}\leq a=a\wedge b$. Then $c\leq a$ so that $\sup\{a,c\}=a$, which precisely translates to $a=a\vee c=a\vee(a\wedge b)$. The remainder of the proof is left for the reader to try.
Mathematics Subject Classification
03G10 no label found06B99 no label found Forums
 Planetary Bugs
 HS/Secondary
 University/Tertiary
 Graduate/Advanced
 Industry/Practice
 Research Topics
 LaTeX help
 Math Comptetitions
 Math History
 Math Humor
 PlanetMath Comments
 PlanetMath System Updates and News
 PlanetMath help
 PlanetMath.ORG
 Strategic Communications Development
 The Math Pub
 Testing messages (ignore)
 Other useful stuff
 Corrections